AKUNTING SUMBERDAYA ALAM LAHAN DAN LINGKUNGAN: KABUPATEN KUTAI TIMUR - Bishry, Rony (Jurnal Teknologi Lingkungan, 2011)
he natural resources utilization for economic development has become the driver ofÃ‚Â land cover and environmental change. Logging and coal production have created dryland. The policy of natural resources utilization for development in Kutai Timur RegencyÃ‚Â has changed the net value of its natural resource capital. For Kutai Timur Regency itÃ‚Â is recorded that between the year of 2004 - 2006, the income of its natural resourcesÃ‚Â was as much as Rp. 13,39 Trillion.Ã‚Â The total change of the economic value of its resource has also created the need forÃ‚Â the environmental cost of Rp. 191 Billion annually since around 95,742 ha has changedÃ‚Â into dry land. However comparing to the need of annual budget to treat the critical land,Ã‚Â the net value of its natural resources capital is relatively high.Ã‚Â